2008
DOI: 10.1113/expphysiol.2008.042143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chemoreflexes on hyperthermic hyperventilation and cerebral blood velocity in resting heated humans

Abstract: We tested the hypothesis that hyperthermic hyperventilation in part reflects enhanced chemoreceptor ventilatory O 2 drive, and that the resultant hypocapnia attenuates ventilatory responses and/or middle cerebral artery mean blood velocity (MCAV mean ) in resting humans. Eleven healthy subjects were passively heated for 50-80 min, causing oesophageal temperature (T oes ) to increase by 1.6• C. During heating, minute ventilation (V E ) increased (P < 0.05), while end-tidal CO 2 pressure (P ET,CO 2 ) and MCAV me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
83
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 33 publications
8
83
1
Order By: Relevance
“…In that study, however, core temperature (oral temperature) was substantially higher in the dehydration trial than rehydration trials (37.69 vs. 37.07°C at 12 h after entering the hot environment). Because elevations in core temperature increase V E at rest (18,19), as it does during exercise, the increased V E seen in the dehydration trial could have been caused by the greater increase in core temperature rather than the increased P osm . Consistent with that idea, before Ex2 in the present study, V E did not significantly differ between the FR Values are means Ϯ SD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In that study, however, core temperature (oral temperature) was substantially higher in the dehydration trial than rehydration trials (37.69 vs. 37.07°C at 12 h after entering the hot environment). Because elevations in core temperature increase V E at rest (18,19), as it does during exercise, the increased V E seen in the dehydration trial could have been caused by the greater increase in core temperature rather than the increased P osm . Consistent with that idea, before Ex2 in the present study, V E did not significantly differ between the FR Values are means Ϯ SD.…”
Section: Discussionmentioning
confidence: 98%
“…We therefore suggest that hypohydration is not a factor for hyperthermic hyperpnea and that other factor(s) could be involved. Although it has been proposed that hyperthermic hyperpnea may be associated with increased sensitivity of peripheral chemoreceptors induced by hyperthermia (53), Fujii et al (18) suggested that the increased sensitivity of peripheral chemoreceptors is not the dominant factor for hyperthermic hyperpnea. Another possible factor that could contribute to hyperthermic hyperpnea is the increase in core temperature, itself (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperventilation induced by increases in body temperature leads to excessive elimination of CO2 and a decrease of arterial PCO2 (PaCO2) both at rest and during prolonged exercise 3,5,6,10,11,[16][17][18] (Fig. 1C).…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%
“…1C). Given that changes in PaCO2 influence V ・ E via chemoreceptors, and that there is a positive linear relationship between V ・ E and PaCO2 19,20) , it seems likely that this hypocapnia suppresses the increase in V ・ E. To investigate the effect of hypocapnia on hyperthermia-induced hyperventilation, we examined the ventilatory response to increasing body temperature in subjects breathing CO2-enriched air to maintain PaCO2 at the eucapnic level at rest 17) and during exercise 14) . We found that V ・ E is unchanged at rest, but that during prolonged exercise at 50% of V ・ O2peak the ventilatory sensitivity to increasing body temperature is 2-3 times greater in CO2-enriched air than in room air (hypocapnic condition) ( Table 1), and that this augmentation is caused by increases in tidal volume and respiratory frequency.…”
Section: Characteristics Of Hyperthermia-induced Hyperventilationmentioning
confidence: 99%